Reformers, Rebels, and Revolutionaries: The Western Canadian Radical Movement, 1899-1919 - McCormack, A. Ross (Heritage, 1977)
The opening of the twentieth century saw a fervour of radical political movements in Western Canada. Ross McCormack explores the constituencies, ideologies, and development of early reformist, syndicalist, and socialist organizations from the 1880s up to the Winnipeg General Strike in 1919. He distinguishes three types of radicals - reformers, rebels, and revolutionaries - who competed with each other to fashion a gneral western constituency. The reformers wanted to change society for the betterment of the workers, but both their aims and methods were moderate, essentially transfering the philosophy and tactics of the British labour movement to the Canadian west. The rebels, militant industrial unionists, periodically battled the Trades and Labour Congress in order to establish unions strong enough to defeat the employers and, if necessary, the state. The revolutionary Marxists were committed to the destruction of industrial capitalism and the establishment of a society controlled by the workers. The book describes the origins of radicalism, traces the histories of the various organizations that expressed its ideals, and discusses the impact of the First World War on the labour movement. Using previously unexplored sources, McCromack has produced the first comprehensive examination of the early history of the radical movement in western Canada, adding an important dimension to our knowledge and understanding of Canadian labour history. --Publisher's description. Contents: The emergence of the socialist movement in British Columbia -- Militant industrial unionism and the first western rebellion -- The ascendancy of the Socialist Party of Canada -- A case study in labourism: Winnipeg 1899-1915 -- The Industrial Workers of the World and militant industrial unionism -- Western radicals and the Great War: the first phase -- Western radicals and the Great War: the second phase.